Development of Co-Chemotherapeutic Agents and Analysis of the Active Substance Content of Red Ginger (Zingiber officinale Var Rubrum rhizoma) in Metastatic Breast Cancer Cells - Laili Nailul Muna; Enny Riyan Hasni; Farhatul Uyun; Erna Wulandari (Biology, Medicine, & Natural Product Chemistry, 2025)
Metastatic breast cancer also known as stage IV breast cancer. Current chemotherapy agents have several limitations, such as resistance events, side effects, and inadequate efficacy in advanced cancer. It is necessary to develop a more effective chemotherapy model, namely the development of co-chemotherapy agents derived from natural ingredients that have activity in counteracting oxidative stress and preventing metastatic breast cancer, namely red ginger. GC-MS analysis of red ginger oleoresin showed the composition of chemical compounds influenced by variants of soxletation time of 60, 120, and 180 minutes. GC-MS analysis showed that this essential oil consists of volatile compounds, mainly from the sesquiterpene group and namely zingiberene, betha-sesquiphellandrene, betha-bisabolene and ar-curcumene. The results of the cytotoxic test analysis of red ginger extract with socletation time for 60, 120 and 180 minutes respectively obtained IC50 data as follows with 45.16 µg/ml, 37.23 µg/ml and 20.2 µg/ml. The compounds contained in red ginger, such as zingiberene, gingerol, shogaol, flavonoids, phenolics, alkaloids, saponins, and tannins, play an important role in its cytotoxic effect against cancer cells. The mechanism by which alpha-Zingiberene induces cell death in cancer cells is mainly through the apoptotic process. The compound causes the release of mitochondrial cytochrome c into the cytoplasm, which then activates caspase-3, an apoptotic enzyme.